Tissue Inhibitor of Metalloproteinase-2 Polymorphisms and Risk for HIV-Associated Neurocognitive Disorder - HariOm Singh; Sushma Jadhav; Dharmesh Samani; Sumitra Nain (Mediators of Inflammation)
The imbalance between MMPs and TIMPs is associated with the HIV dissemination tissue damage pathology neurodegenerative disorders, including HAND. Genetic variations in the TIMP gene may modulate the neurocognitive disorder in HIV patients. Hence, we evaluated the genetic variants of TIMP-2 (-418G/C, 303G/A) gene with the risk of HAND. Genotyping of TIMP-2 polymorphism was performed in 50 patients with HAND, 100 no HAND, and 154 healthy controls by PCR-RFLP. TIMP-2 -418GC and 303AA genotypes represented a predominant risk for HAND severity (OR=1.55, P=0.30; OR=4.58, P=0.24). The variant -418CC genotype, -418A allele, had exhibited a significant risk for the acquisition of HAND (OR=12.55, P=0.026; OR=2.66, P=0.004). TIMP-2 303GA, 303AA genotype, and 303A allele evinced a higher risk for HAND severity (OR=1.82, P=0.14; OR=1.70, P=0.63; and OR=1.68, P=0.12). In HIV patients, TIMP-2 -418CC genotype and -418C allele significantly occurred in comparison to healthy controls (OR=10.10, P=0.006; OR=2.02, P=0.009). In the intermediate and early HIV disease stage, TIMP-2 -418CC genotype was significantly increased compared with healthy controls (11.1% vs. 1.3%, OR=14.63, P=0.01; 16.9% vs. 1.3%, OR=14.51, P=0.002). In patients with HAND among tobacco and alcohol users, TIMP-2 -418CC genotype displayed a risk for HAND severity (OR=3.96, P=0.26; OR=4.83, P=0.19). On multivariate logistic regression, TIMP-2 303AA genotype, advanced stage, and gender had a risk for HAND severity (OR=28.98, P=0.02; OR=2.35, P=0.070; and OR=2.36, P=0.04). In conclusion, TIMP-2 -418G/C polymorphism independently, along with alcohol and tobacco, may have an impact on the acquisition of HAND and its severity. TIMP-2 303G/A polymorphism bare a risk for HAND severity.